Design and Manufacture of Automatic Sheet Metal Bending Machine Tools In The Press Brake Section - Heri Wibowo; Hanif Nur Hidayat (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2025)
Design and manufacture of automatic sheet metal bending machine tools in the press brake section with the aim of being able to streamline the operating time of bending machines in the Orange Teknik workshop. The main obstacle is that the bending machine is operated manually because it still uses an analog system. The main goal in creating this innovative tool is to assist the operation of a sheet metal bending machine so that it saves time and makes it easier to determine the results of the bending angle. In the process of designing and manufacturing automatic tools, it begins with an analysis of the problems in Orange Engineering, Literature Study, carrying out the design, manufacture and assembly of tools for bending machines, searching for bending data and analyzing data, creating equation formulas and ending with automatic data validation. The result shows that as the thickness of the plate used increases, the required punch force decreases, or the rotary encoder value becomes smaller to achieve the same angle as thinner plates. The effect of plate material variation in the bending process shows that the punch force applied in the press brake system is greater for black iron plates. Similarly, the rotary encoder value is higher to achieve the same bending angle compared to stainless steel plates.